Managing digital archival collections by integrating Archivematica, AtoM and VuFind software: the University of Thessaly Historical Archive case - Clapsopoulos, Ioannis; Laliotou, Ioanna; Doropoulos, Stavros; Fanakis, Apostolos; Bourdakis, Vassilis; Stoyannidis, Yannis; Pentazou, Ioulia; Kalaouzis , George; Selitsaniotis, Theodore (Journal of Integrated Information Management, 2024)
Purpose – The great number of documents and records produced by universities leads to large archival collections within these Institutions. As a result, libraries and archival units apply new and innovative information systems to manage and exploit their archival collections for education and research purposes. Design/methodology/approach – The current research took place under the THE.ME.DO.COM EPAnEK (2014-2020) project, which mainly aimed to develop two web platforms for the preservation, documentation, management, and dissemination of the University of Thessaly archival collections, which constituted its Historical Archive. For this purpose, the Archivematica, AtoM and VuFind open-source information systems were configured and integrated, while innovative metadata creation coding was created for the project. Findings – Digital archival items were preserved and enriched with high-quality metadata in Archivematica, uploaded and described according to international standards in AtoM and distributed with smart search routines with VuFind. The integrated platform implementation resulted in an efficient automated approach to managing the University of Thessaly archives and archival collections, which comprised different digital object formats and included a high volume of digital items, making THE.ME.DO.COM a very successful project example. Originality/value – The University of Thessaly Historical Archive was used as a paradigm for implementing a new way to deal with complex archival collections. Other University Libraries or Archival Services could efficiently utilise the project results.